Mechanism of miR-143-3p inhibiting proliferation, migration and invasion of osteosarcoma cells by targeting MAPK7. Issue 1 (4th December 2019) - Hou, Yu; Feng, Helin; Jiao, Jianbao; Qian, Ligang; Sun, Bo; Chen, Pingtao; Li, Qinggui; Liang, Zhixing
Abstract: Objective: To investigate the effects of miR-143-3p and MAPK7 on the proliferation, migration, and invasion of U2OS human osteosarcoma (OS) cells. Methods: The expression of miR-143-3p and MAPK7 in U2OS cells were detected by qRT-PCR, and the protein level of MAPK7 was measured by western blot assay. The targeting relationship between miR-143-3p and MAPK7 was predicted by TargetScan and verified by dual luciferase reporter assay. MTT and Transwell assays were used to detect cell viability, migrated cells and invaded cells of U2OS cells. Results: Compared with hFOB1.19 cells, the expression of miR-143-3p was down-regulated and MAPK7 was up-regulated in U2OS cells. Cell viability, migration and invasion ability significantly decreased induced by miR-143-3p overexpression or MAPK7 knockdown in U2OS cells. The results of dual luciferase reporter assay indicated that miR-143-3p interacted with MAPK7. Furthermore, overexpression of MAPK7 could reverse the inhibitory effects on cell proliferation, migration and invasion in U2OS cells induced by miR-143-3p mimics. Conclusion: miR-143-3p could inhibit proliferation, migration and invasion of U2OS cells by targeting MAPK7.